The Influence of Return on Assets, Return on Equity and Current Ratio on Capital Structure in Consumer Goods Companies Listed on the Indonesia Stock Exchange - Yenni Martok; Losiana Tannika (Proceeding of International Conference on Global Innovation and Trend in Economics, 2022)
The objective of this research is to analyze the influence of return on assets, return on equity, and current ratio toward capital structure in consumer goods companies listed on the Indonesia Stock Exchange. The population of this research is the consumer goods companies listed in Indonesia Stock Exchange during 2013-2017. Further, with the employed purposive sampling and determined criteria, 20 companies are chosen as the samples. The data analysis method applied is multiple linear regression which is processed through SPSS 25. The result of this research shows that return on assets and current ratio have a significant negative impact toward capital structure partially, return on equity have a significant negative impact toward capital structure partially. On the other hand, return on assets, return on equity, and current ratio have significant simultaneous impact toward capital structure. Meanwhile, Institutional Ownership, Profitability, and Independent Commissioner do not have a significant impact toward Tax Avoidance.